The Influence of Work Ethics and Training on the Performance of Teachers and Educational Personnel - Marwanto, Marwanto; Ahmaluddin, Ahmaluddin (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2024)
One of the efforts an organization can make to maintain employee performance is by paying attention to work ethic and employee motivation. Having qualified employees does not necessarily guarantee good performance, and vice versa. Employees who have not yet shown their best performance may be influenced by several factors, including: 1) a high number of employees not attending work; 2) low job satisfaction; and 3) poor work ethic among the employees. Therefore, the aim of this study is to determine: 1) the influence of work ethic on performance; 2) the influence of training on performance; and 3) the combined influence of work ethic and training on the performance of teachers and educational staff at SMPN 1 Punggur, Central Lampung Regency. This study uses a descriptive quantitative research method with 34 respondents. The analysis used is simple and multiple regression. Based on the data analysis, it was found that, partially, there is an influence of Work Ethic (X1) and training (X2) on Performance (Y) at SMPN 1 Punggur, Central Lampung Regency. Additionally, the combined influence of Work Ethic and Training has an impact on performance at SMPN 1 Punggur, Central Lampung Regency, with an effect level of 83.9 percent.